The role of import intermediary companies in the Russian imports from the EU A case study of a Russian industrial company’s point of view on import intermediaries - Ionin, Mihail (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
The literature on agency suggests different implications for the use of export intermediaries. However, only few studies provide a view on import intermediaries. This thesis tries for its part to fill this research gap by studying the import intermediaries in the EU–Russia trade from a Russian industrial company’s point of view. The aim is to describe import intermediation and explain the need for import intermediary companies in the EU–Russia trade. The theoretical framework of this thesis originates from an article by Peng and York (2001), in which they study the performance of export intermediaries. This thesis applies resource-based theory, transaction cost theory and agency cost theory, following the idea of Peng and York. The resource-based theory approach is utilised for describing an ideal import intermediary company, and transaction cost theory provides a basis for understanding the benefits of using the services of import intermediary companies, while agency cost theory is applied in order to understand the risks the Russian industrial company faces when it decides to use the services of import intermediaries. The study is performed in the form of a case interview with a representative of a major Russian metallurgy company. The results of the study suggest that an ideal intermediary has the skills required specifically for the imports process, in order to save time and money of the principal company. The intermediary company helps reducing the amount of time the managers and the staff of the principal company use to make imports possible, thus reducing the salary costs and providing the possibility to concentrate on the company’s core competencies. The benefits of using the services of import intermediary companies are the reduced transaction costs, especially salary costs that are minimised because of the effectiveness and specialisation of import intermediaries. Intermediaries are specialised in the imports process and thus need less time and resources to organise the imports. They also help to reduce the fixed salary costs, because their services can be used only when needed. The risks of being misled by intermediaries are minimised by the competition on the import intermediary market. In case an intermediary attempts fraud, it gets replaced by its rival.